DNA-binding function of c-Myb R2R3 around thermal denaturation temperature - Maki Kawasaki (Biophysics and Physicobiology, 2021)
The minimum DNA-binding domain of the transcriptional factor c-Myb R2R3 remarkably fluctuates in the solution. In the present study, we evaluated the protein fluctuation of R2R3 C130I mutant, R2R3*, on its DNA-binding and folding thermodynamics. DNA-binding analysis using isothermal titration calorimetry revealed that the heat capacity change determined from the correlation between temperature and binding enthalpy change is highly negative above 35°C, indicating that the fluctuation increases with increasing temperature and elevates the conformational change on DNA binding. The results were in accordance with those of differential scanning calorimetry, which revealed that the heat capacity corresponding to thermal denaturation gradually increased above 35°C, followed by the broad transition peak. In contrast, the transition peak of R2R3* in the DNA-bound state was sharper and larger than that in the DNA-unbound state. The fluctuating form could transform into lesser fluctuating form upon DNA binding, resulting in a larger enthalpy change for denaturation of R2R3* in the DNA-bound state. It should also be noted that R2R3* could specifically bind to DNA around thermal denaturation temperature. This would be due to proteins with numerous fluctuations. Moreover, we discuss specific and non-specific DNA binding accompanied by the conformational change between well-ordered and disordered forms of R2R3* observed around the denaturation temperature.